Technological affordances of risk and blame: the case of the electronic prescription service in England. Issue 5 (19th March 2014) - Petrakaki, Dimitra; Waring, Justin; Barber, Nicholas
Abstract Information and communication technology (ICT) is often presented by health policymakers and software designers as a means for reducing clinical risk, leading to safer clinical practice. Studies have challenged this view, showing how technology can produce new or unanticipated risks. Although research seeks to objectively identify these risks, we recognise that technological risks are socially constructed through the interaction of technology and practice. The aim of this article is to explore how technology affords opportunities for the social construction and control of risk in health care settings. Drawing upon a study of the electronic prescription service introduced in the National Health Service in England, we make three arguments. Firstly, as technology interacts with social practice (for example, through policy and the design and use of ICT) it affords opportunities for the construction of risk through its interpretive flexibility, transformative capacity and materiality. Secondly, social actors interpret these risks within and across professional boundaries and cultures. Thirdly, the social construction of risk affords certain implications to policymakers, designers and users of health ICT, specifically a reordering of power and responsibility and a recasting of questions of blame. These, in turn, raise questions concerning the boundaries and bearers of responsibility.